The influence of traditional and new processing technologies on the structure and function of food polysaccharide. Issue 7 (24th June 2020) - Benchamas, Gunsriwiang; Huang, Shiyu; Huang, Gangliang
Abstract : The influence of traditional processing technologies and new technologies on the structure and function of food polysaccharide was investigated and discussed. Abstract : Food processing is the method of transforming raw materials into food or food into other forms through physical or chemical technology and is an important means to extend the shelf life of food. The influence of processing technology on the structure and functional characteristics of polysaccharide was analyzed for the three aspects of dehydration processing technology, hot processing technology and new processing technology to provide reference for prolonging the shelf life of food and protecting its nutritional value.